2020
DOI: 10.1037/dev0001100
|View full text |Cite
|
Sign up to set email alerts
|

Children flexibly compare their confidence within and across perceptual domains.

Abstract: How does a person make decisions across perceptual boundaries? Here, we test the account that confidence constitutes a common currency for perceptual decisions even in childhood by examining whether confidence can be compared across distinct perceptual dimensions. We conducted a strict test of domain-generality in confidence reasoning by asking 6-to 7-year-olds to compare their confidence in 2 decisions, either from the same perceptual dimension (e.g., number vs. number) or from two different perceptual dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Although our findings are not what we expected given previously reported correlations between self and other tasks, they are consistent with other recent evidence against an SDT account of confidence judgments. For example, using the same relative confidence task in 6-9-year-olds, Baer et al (2018) reported correlations between confidence tasks that use independent representations, which should be uncorrelated according to pure SDT principles (and see Baer & Odic, 2020a). In the Supplemental Material, we partially replicate this finding using data from Experiment 1: area and number confidence judgments were correlated, but neither correlated with emotion confidence.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Although our findings are not what we expected given previously reported correlations between self and other tasks, they are consistent with other recent evidence against an SDT account of confidence judgments. For example, using the same relative confidence task in 6-9-year-olds, Baer et al (2018) reported correlations between confidence tasks that use independent representations, which should be uncorrelated according to pure SDT principles (and see Baer & Odic, 2020a). In the Supplemental Material, we partially replicate this finding using data from Experiment 1: area and number confidence judgments were correlated, but neither correlated with emotion confidence.…”
Section: Discussionmentioning
confidence: 68%
“…We modified the Confidence Task so that rather than making prospective judgments about their success, children evaluated their confidence retrospectively (Baer & Odic, 2019, 2020a. Like before, children saw four warm-up trials of the 'blobs game' (area discriminations) before being introduced to the confidence portion of the task.…”
Section: Confidence Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…Guggenmos et al, 2016;Hainguerlot et al, 2018). Furthermore, confidence, typically defined as the subjective probability of being correct, may constitute a common currency with which distinct perceptual decisions or tasks can be compared (de Gardelle & Mamassian, 2014;de Gardelle et al, 2016;Baer & Odic, 2020) and prioritized within a single individual (e.g. Aguilar-Lleyda et al, 2020;Carlebach & for global evaluations of performance has also been found in other types of tasks, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Generality and specificity of metacognitive mechanisms, respectively, is then evaluated based on the shared variance in metacognitive performance (i.e., the capacity to estimate the accuracy of task performance) that is observed across tasks. Only few studies have addressed the question more directly by comparing confidence judgments not only within tasks but also across tasks (e.g., Baer & Odic, 2020 ; de Gardelle, Le Corre, & Mamassian, 2016 ; de Gardelle & Mamassian, 2014 ). Despite these different approaches, findings mainly point toward a common metacognitive mechanism—at least within the perceptual domain.…”
Section: Introductionmentioning
confidence: 99%